Molecular Recognition of Sialic Acid End Groups by Phenylboronates - Djanashvili, Kristina; Frullano, Luca; Peters, Joop A. (Chemistry : a European journal, 2005)
A multinuclear NMR study of the interaction between phenylboronic acid (PBA) and sialic acid (Neu5 Ac) has been performed. The latter compound is known to be overexpressed on the cell surface of tumor cells. The results of this investigation suggest that the binding of PBA to sialic acid is pH dependent. 17O NMR experiments with glycolic acid as the model compound prove that an interaction at the α‐hydroxycarboxylate occurs at pH < 9, while a study with threonic and erythronic acids shows that the PBA group interacts selectively with the vicinal diol functions at higher pH. Similarly, Neu5 Ac binds PBA through its α‐hydroxycarboxylate at low pH (< 9) and through its glycerol side chain at higher pH values. The conditional stability constant of the phenylboronate ester at pH 7.4 is 11.4. On cell surfaces, sialic acid is connected to the neighboring sugar unit through the 2‐hydroxy group. To mimic this the 2‐α‐O‐methyl derivative of Neu5 Ac was included in this study. The erythro configuration of the hydroxy substituents prevents stable‐complex formation at positions C7 and C8 and, consequently, the strongest interaction is observed at positions C8 and C9, leading to a five‐membered 2‐boron‐1,3‐dioxalate. In addition, a relatively small amount of the C7–C9 six‐membered complex was observed. Molecular modeling studies confirm that the C8–C9 boronate complex has the lowest energy. A potential targeting moiety in artificial sugar receptors, phenylboronic acid (PBA), can bind sialic acid in two different modes: at the α‐hydroxycarboxylate function or at the glycerol tail. This interaction is very pH dependent, and the formation of several species is possible (see picture). Sialic acid residues in glycoproteins are recognized by PBA through boronate ester formation at the glycerol side chain.